Association between ultra-processed food consumption and risk of breast cancer: a systematic review and dose-response meta-analysis of observational studies - Shu, Long; Zhang, Xiaoyan; Zhu, Qin; Lv, Xiaoling; Si, Caijuan (Frontiers in Nutrition, 2023)
Background: Some epidemiological studies have examined the association between consumption of ultra-processed food(UPF) and the risk of breast cancer. However, the results were inconsistent.Therefore, we carried out a systematic review and dose-response meta-analysis to examine whether an association exists between high consumption of UPF and breast cancer risk.Methods: PubMed/MEDLINE, ISI Web of Science, EBSCO and CNKI databases were systematically searched from inception to May 2023. The summary relative risks (RRs) and 95% confidence intervals(CIs) associated with UPF consumption and breast cancer were calculated using a random-effects model(DerSimonian-Laird method).Heterogeneity between included studies was examined using the Cochran's Q test and I-square(I 2 ) statistics. Publication bias was studied by visual inspection of funnel plot asymmetry and Begg's and Egger's tests.Results: Overall, six articles involving 462,292 participants, were eligible to be included in this study. Compared to the lowest consumption, highest consumption of UPF was related to a higher risk of breast cancer(RR=1.10; 95%CI:1.00-1.22, P=0.056). Besides, the linear dose-response analysis showed that each 10% increment in UPF consumption was related to a 5% higher risk of breast cancer(RR=1.05; 95%CI: 1.00-1.10, P=0.048). Subgroup analyses suggested that UPF consumption was positively associated with breast cancer risk in case-control studies(RR=1.13; 95%CI: 1.01-1.26, P=0.028). Additionally, there was also a significant positive association between UPF consumption and breast cancer risk in the subgroup with sample size<5000(RR=1.17; 95%CI: 1.02-1.35, P=0.028).Conclusions: Our results indicate that higher consumption of UPF is slightly related to a higher risk of breast cancer. Further studies in particular of large prospective cohort studies are warranted to confirm these results.